Comparative evaluation of Green Tea- Aloe Vera mouthwash and chlorhexidine 0.2% on gingival indices (A randomized clinical trial) - Naser Sargolzaie; Omid Rajabi; Hamidraza Arab; Habibollah Esmaele; Atefeh Ehteshamfar (Mashhad University of Medical Sciences, 2016)
Introduction: Nowadays in the field of dentistry, there is a trend to encourage the use of herbal and natural products. The high level of clinical research in terms of considering green tea and aloe vera, with various functionality for individual use is a typical example. The purpose of this randomized, controlled, and double-blind study was to evaluate comparative evaluation of green tea-aloe vera mouthwash and chlorhexidine 0.2% on gingival indices. Methods: A total of 60 patients (26 women and 34 men) with periodontal disease were randomly allocated into one of the three double blind groups, 20 in each, to receive the following treatments :(1) 0.2% chlorhexidine, (2) green tea-aloe vera and  (3) distilled water. Plaque and gingival indices were evaluated on the day of the beginning of the experiment and 14 days postoperative. Subjects were asked to rinse their mouth with the mouth rinse, twice a day, during a 14-day period. Paired t-test was used to test the mean difference on 0 and 14 days, respectively. One way analysis of variance (ANOVA) was used to compare the mean difference between the groups while Tukey test was used for multiple comparisons. Results: Chlorhexidine 0.2%, green tea - aloe vera and placebo reduced the plaque index by 0.17±0.14, 0.10±0/08 and 0.02±0.18, respectively, with a statistical significance of p=0.008. This difference was related to Chlorhexidine 0.2% and green tea - aloe vera with Placebo. There exist a significant difference of p=0.001 in the bleeding index  between the three groups, and this difference was related to Chlorhexidine 0.2% and green tea - aloe vera with placebo. Conclusion: Green tea -aloe vera   mouthwash improves periodontal health status. Therefore, it can be used to improve oral and dental health status.